PAVING BLOCK MARKETING ANALYSIS AT CV MEKAR JAYA PEKANBARU - Widiyanti, Widiyanti; Wijoyo, Hadion (International Journal of Business and Information Technology, 2020)
Based on the background that has been stated, the problem formulation is How is the paving block marketing system at CV Mekar Jaya Pekanbaru? From the formulation of the problem, the research objective was determined, namely to determine the paving block marketing system at CV Mekar Jaya Pekanbaru. To complete the data, the authors use types and sources of data, namely primary data that comes from respondents' responses. Secondary data, namely data obtained by collecting materials in connection with sales data, sales price lists, and distribution channels. While the data collection techniques are; interviews and questionnaires. From the research results, it can be concluded that based on the results of research regarding the product, the overall response of the respondents obtained a total score of 1220. This means that the marketing of paving blocks at CV Mekar Jaya seen from the product is considered very good. From the research results obtained a total score of 704. This means that the marketing of paving blocks at CV Mekar Jaya seen from the price is considered good. From the overall responses of the respondents, a total score of 337 was obtained. This means that the marketing of paving blocks at CV Mekar Jaya, seen from the promotion, is considered quite good. From the overall response of the respondents, a total score of 754 was obtained. This means that the marketing of paving blocks at CV Mekar Jaya, seen from the product, is considered quite good